MODEL PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) - Wahanisa, Rofi (Faculty of Law, Universitas Sebelas Maret, 2015)
AbstractForest management must consider the cultural values of society, aspirations and perceptions, and involve local communities in forest management in the presence of community-based forest management (PHBM). One of the areas that have the potential wealth of natural / forest resources is Kendal. Formulation of the problem, 1) forest management in Kendal?, 2) The role and participation in PHBM in Kendal?, 3) Barriers in PHBM in Kendal ?. This research is a kind of juridical empirical research. Engineering analysis was performed by descriptive analysis. Based on the results of the study, 1) Implementation of forest management in Kendal done involving the community, with the PHBM models, 2) The role and participation of the community with the establishment of the Institute of Forest Village Community (LMDH) / Forest Village Community Association (PMDH), 3) Barriers, less fast accessing information with a range of obstacles. Advice that can be given, among others, 1) Model Forest Management (PHBM) is considered effective. 2) Increasing community participation in the management of forest resources. 3) In order to overcome the obstacles of rural communities to be pro-active with each other to obtain information for the development of forest resource management. AbstrakPengelolaan hutan harus memperhatikan nilai-nilai budaya masyarakat, aspirasi dan persepsi masyarakat, dan melibatkan masyarakat setempat dalam pengelolaan hutan dengan adanya pengelolaan hutan berbasis masyarakat (PHBM). Salah satu daerah yang memiliki potensi kekayaan alam / sumber daya hutan adalah Kabupaten Kendal. Perumusan masalah, 1) Pengelolaan hutan di Kabupaten Kendal ?, 2) Peran dan partisipasi masyarakat dalam PHBM di Kabupaten Kendal ?, 3) Hambatan dalam PHBM di Kabupaten Kendal?. Penelitian ini adalah jenis penelitian yuridis empiris. Tekhnik analisis dilakukan secara deskriptif analisis. Berdasarkan hasil penelitian, 1) Pelaksanaan pengelolaan hutan di Kabupaten Kendal dilakukan mengikutsertakan masyarakat, dengan model PHBM, 2) Peran dan partisipasi masyarakat dengan pembentukan Lembaga Masyarakat Desa Hutan (LMDH) / Perkumpulan Masyarakat Desa Hutan (PMDH), 3) Hambatan, kurang cepat mengakses informasi dengan berbagai kendala. Saran yang bisa diberikan antara lain, 1) Model pengelolaan hutan bersama masyarakat (PHBM) dianggap efektif.2) Meningkatkan peran serta masyarakat dalam pengelolaan sumber daya hutan. 3) Untuk mengatasi hambatan masyarakat desa bersikap saling pro aktif untuk memperoleh informasi untuk pengembangan pengelolaan sumber daya hutan.